2019
DOI: 10.1002/ange.201907082
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Driven CO2 Reduction by Mesoporous Carbon Nitride Modified with Polymeric Cobalt Phthalocyanine

Abstract: The integration of molecular catalysts with low-cost, solid light absorbers presents apromising strategy to construct catalysts for the generation of solar fuels.H ere,w er eport aphotocatalyst for CO 2 reduction that consists of apolymeric cobalt phthalocyanine catalyst (CoPPc) coupled with mesoporous carbon nitride (mpg-CN x )a st he photosensitizer.T his precious-metal-free hybrid catalyst selectively converts CO 2 to CO in organic solvents under UV/Vis light (AM 1.5G, 100 mW cm À2 , l > 300 nm) with ac oba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…To the best of our knowledge, lower activity in organic solvents was due to phase separation. [62,63] The influence of the scavenger concentration on the photocatalytic performance of the optimized composite was investigated. These results are shown in Figure S6e.…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, lower activity in organic solvents was due to phase separation. [62,63] The influence of the scavenger concentration on the photocatalytic performance of the optimized composite was investigated. These results are shown in Figure S6e.…”
Section: Resultsmentioning
confidence: 99%
“…Cobalt nitrides have proved beneficial for CO 2 RR because they offer more surface base sites of adsorption of CO 2 and the generation of more active sites [ 140 , 141 , 142 , 143 , 144 , 145 , 146 ]. Peng et al reported the highly efficient CO 2 RR cobalt nitride catalysts (700-Co 5.47 N/C) in an aqueous electrolyte.…”
Section: Cobalt Catalysts For Co 2 Reductionmentioning
confidence: 99%
“…Reisner prepared a photocatalyst based on mesoporous graphitic carbon nitride (mpg-CNx), incorporating the polymeric Co(II) Pc 21 ( Figure 9 ) [ 125 ]. Under full solar spectrum irradiation, the photocatalyst mpg-CNx:Pc 22 (~12 mmol Co/g catalyst) generated a 1000 mmol CO/g catalyst after 48 h with 85% selectivity (TON CO = 85), a 65% increase in activity compared to that under visible light alone (607 mmol CO/g after 48 h, TON CO = 51).…”
Section: Materials Photo-applications Of Phthalocyaninesmentioning
confidence: 99%